2004
DOI: 10.1095/biolreprod.103.023853
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Growth Hormone Treatment from Day 35 to 80 of Gestation Alters Nutrient Partitioning in Favor of Uteroplacental Growth in the Overnourished Adolescent Sheep1

Abstract: Overnourishing the pregnant adolescent ewe promotes maternal tissue synthesis at the expense of placental growth and leads to a major reduction in lamb birth weight at term. Growth hormone (GH) secretion is attenuated in these overnourished dams and the maternal somatotrophic axis may play a key role in coordinating nutrient usage in the pregnant adolescent. Thus we investigated whether increasing maternal GH during the period of rapid placental proliferation alters nutrient partitioning between the maternal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 51 publications
6
43
3
2
Order By: Relevance
“…This approach was critical to determine the basis of the previously observed changes in placental development and function in late gestation. The study demonstrated that placental mass per se is not perturbed by maternal overfeeding until sometime during the final third of pregnancy and as such confirms previous studies in which the pregnancies were terminated at single points coincident with either mid (Wallace et al 2004b or late (Wallace et al 2000(Wallace et al , 2002a(Wallace et al , 2002b gestation. Moreover, the data revealed for the first time that the fetuses of overnourished dams may be initially on a higher growth trajectory than control fetuses between day 50 and 90 of gestation, with fetal weight being 11% greater by day 90 in the H group.…”
Section: Discussionsupporting
confidence: 88%
“…This approach was critical to determine the basis of the previously observed changes in placental development and function in late gestation. The study demonstrated that placental mass per se is not perturbed by maternal overfeeding until sometime during the final third of pregnancy and as such confirms previous studies in which the pregnancies were terminated at single points coincident with either mid (Wallace et al 2004b or late (Wallace et al 2000(Wallace et al , 2002a(Wallace et al , 2002b gestation. Moreover, the data revealed for the first time that the fetuses of overnourished dams may be initially on a higher growth trajectory than control fetuses between day 50 and 90 of gestation, with fetal weight being 11% greater by day 90 in the H group.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in caruncle expression of IGFBP-1 can be attributed to two possible mechanisms. First, IGFBP-1 is inversely regulated by insulin (Suikkari et al 1989), and it has been shown previously that GH administration during gestation leads to hyperinsulinemia (Wallace et al 2004). Given that we achieved significant stimulation of IGF-I similar to that reported by Wallace et al one could reason that we generated a similar insulin response that reduced caruncle expression of IGFBP-1.…”
Section: Discussionsupporting
confidence: 74%
“…Wallace et al initiated GH administration to adolescent ewes at the appropriate time (day C D WRIGHT and others . GH effects on placental and fetal development 35); however, the GH treatment continued to day 80 (Wallace et al 2004), well past the reported cessation of oGH expression in the placenta (Lacroix et al 1996(Lacroix et al , 1999. Although Wallace et al reported an increase in placental weight in the over-nourished adolescent ewes with singletons; these ewes are predisposed to placental and fetal growth restriction due to the high plane of nutrition.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations